Hubungan Tingkat Pengetahuan Remaja dengan Perilaku Kesehatan Reproduksi Remaja pada Siswa di SMK Generasi Mandiri Gunung Putri Bogor - Hasdiana, Hasdiana; Barkah, Asep (Universitas Malahayati, 2025)
ABSTRACT WHO in 2022 reported that every year an estimated 21 million girls aged 15-19 years in developing countries become pregnant and around 12 million of them give birth. In Indonesia, according to the Indonesian Health Survey Report (2023), the proportion of women aged 10-19 years who have ever been pregnant is 64.4% and 12.8% are currently pregnant. Unwanted pregnancy is as much as 40%. Meanwhile, according to data from the National Population and Family Planning Agency in 2023, unwanted pregnancies in Indonesia reached 17.5%. Of the total adolescent population (aged 14-19 years), there are 19.6% cases of unwanted pregnancies. Adolescent problems related to reproductive health behavior are all rooted in a lack of information, knowledge and awareness to achieve reproductive health. Knowing the relationship between the level of adolescent knowledge and adolescent reproductive health behavior among students. Analytical with cross sectional design. The sample in this research was 47 students from class XI of SMK Generasi Mandiri. The sampling technique uses Random Sampling. The frequency distribution of adolescent knowledge was mostly good (55.3%) and adolescent reproductive health behavior was good (68.1%). There is a relationship between the level of adolescent knowledge and adolescent reproductive health behavior among students (p. value 0.000). There is a relationship between the level of adolescent knowledge and adolescent reproductive health behavior among students. It is hoped that health workers will carry out outreach about Adolescent Reproductive Health in youth organizations and in schools. Keywords: Knowledge, Health Behavior, Reproduction ABSTRAK WHO tahun 2022 melaporkan bahwa setiap tahun diperkirakan 21 juta anak perempuan berusia 15-19 tahun di negara berkembang hamil dan sekitar 12 juta di antaranya melahirkan. Di Indonesia, menurut Laporan Survei Kesehatan Indonesia (2023), proporsi perempuan usia 10-19 tahun pernah hamil 64,4% dan 12,8% sedang hamil. Kehamilan yang tidak diinginkan sebanyak 40%. Sementara itu, menurut data dari Badan Kependudukan dan Keluarga Berencana Nasional tahun 2023, kehamilan tidak diinginkan di Indonesia mencapai 17,5%. Dari jumlah penduduk Remaja (usia 14-19 tahun) terdapat 19,6% kasus kehamilan tak diinginkan. Permasalahan remaja yang berkaitan dengan perilaku kesehatan reproduksi yang semuanya berakar dari kurangnya informasi, pengetahuan dan kesadaran untuk mencapai keadaan sehat secara reproduksi. Mengetahui hubungan tingkat pengetahuan remaja dengan perilaku kesehatan reproduksi remaja pada siswa. Analitik dengan rancangan cross sectional. Sampel dalam penelitian ini adalah sebagian siswa/siswi kelas XI SMK Generasi Mandiri sebanyak 47 orang. Teknik pengambilan sampel menggunakan Random Sampling. Distribusi frekuensi pengetahuan remaja sebagian besar baik (55,3%) dan perilaku kesehatan reproduksi remaja baik (68,1%). Ada hubungan tingkat pengetahuan remaja dengan perilaku kesehatan reproduksi remaja pada siswa (p. value 0,000). Ada hubungan tingkat pengetahuan remaja dengan perilaku kesehatan reproduksi remaja pada siswa. Diharapkan tenaga kesehatan melakukan sosialisasi tentang Kesehatan Reproduksi Remaja di organisasi – organisasi remaja maupun di sekolahan. Kata Kunci: Pengetahuan, Perilaku Kesehatan, Reproduksi